Filtering the Beer : A Permanent and Transitory Decomposition - Clark, Peter (IMF Working Papers; Working Paper, 2000)
In this paper we extend the BEER (Behavioral Equilibrium Exchange Rate) approach which identifies an estimated equilibrium relationship between the real exchange rate and economic fundamentals. Here the economic fundamentals are decomposed using Johansen cointegration methods into transitory and permanent components, with the latter used to estimate the Permanent Equilibrium Exchange Rate, or PEER, for the U.S. and Canadian dollars and the pound sterling. The BEER and the PEER move closely together for the U.S. and Canadian dollars and generally track the actual exchange rate. By contrast, for the pound sterling the BEER and the PEER diverge sharply, with the latter following the actual exchange rate quite closely.